Dipeptidyl peptidase-IV enzymatic activity bearing molecules in human brain tumors - good or evil? - Bušek, Petr; Stremeňová, Jarmila; Šedo, Aleksi (Frontiers in bioscience, 2008)
Dipeptidyl peptidase-IV (DPP-IV) represents a unique proteolytic activity cleaving N-terminal X-Pro dipeptides. In addition to canonical DPP-IV/CD26, a number of other molecules have been discovered which exhibit DPP-IV-like enzymatic activity and various degree of structural similarity. These comprise enzymatically active fibroblast activation protein-alpha, DPP-II, DPP8, DPP9 and enzymatically inactive DPP6 and DPP10 that have been grouped as "DPP-IV activity and/or structure homologues" (DASH). Because the enzymatically active DASH can share similar sets of biologically active substrates and are frequently coexpressed within single cell or on tissue level, it is tempting to consider their participation on biological function(s) previously attributed to DPP-IV/CD26. It is speculated that disrupted expression and enzymatic activity of some DASH might corrupt the message carried by their substrates, with consequent promotion of abnormal cell behavior. Thus, modulation of activity of a particular enzyme using e.g. inhibitors, specific antibodies or modifying its expression may be an attractive therapeutic concept in cancer treatment. This review summarizes current knowledge of the expression and possible function of DPP-IV enzymatic activity bearing molecules in human brain tumors.
Keywords: gliom; Dipeptidyl Peptidase 4; lidé; Brain Neoplasms; regulace genové exprese u nádorů; Cell Differentiation; nádory mozku; proteasy; buněčná diferenciace; Brain; chemokiny; Gene Expression Regulation, Enzymologic; Financing, Organized; Humans; dipeptidylpeptidasa 4; Gene Expression Regulation, Neoplastic; biologické modely; Chemokine CXCL12; Chemokines; Glioblastoma; glioblastom; receptory CXCR4; Glioma; mozek; regulace genové exprese enzymů; financování organizované; Receptors, CXCR4; Peptide Hydrolases; chemokin CXCL12; Models, Biological